The Influence of Internal Control System and Accountability of Village Fund Allocation Management on Village Financial Performance - Seger Priantono; Elok Dwi Vidiyastutik (Universitas Pendidikan Ganesha, 2022)
This study aims to analyze the influence of internal control and accountability systems simultaneously and partially on the financial performance of the village. The type of research used is quantitative research with a causal associative approach. The subjects of the study were all parties directly involved in the management of village funds allocation in Gending District of Probolinggo Regency amounted to 41 people. This type of data in the form of primary data is obtained through questionnaires and analyzed using multiple regression analysis. The results showed that the internal control and accountability system simultaneously had a significant effect on the financial performance of the village and the internal control system and partial accountability also had a significant effect on the financial performance of the village in the Gending Subdistrict of Probolinggo Regency. Internal control is required to provide and present financial statements in accordance with the laws and regulations on a regular basis, the prevailing regularity will provide effectiveness to financial performance as a mirror of the success that has been done by employees.